2018
DOI: 10.1002/app.46388
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hexane succinate) plasticizer designed for poly(vinyl chloride) with a high efficiency, nontoxicity, and improved migration resistance

Abstract: Poly(hexane succinate) (PHS) was designed as an alternative type of polyester plasticizer for the modification of poly(vinyl chloride) (PVC). The plasticizing effect of PHS was studied and compared with the traditional dioctyl phthalate (DOP) plasticizer. The results show that the PVC plasticized by PHS had the lowest tensile strength of 15.3 MPa and the highest elongation at break of 105.1% when 35 phr PHS was added. It also exhibited a lower glass‐transition temperature than PVC plasticized by DOP (PVC–DOP);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…PVC-DEHT film (PVC1) had the lowest weight loss values in distilled water, followed very closely by all the other plasticized systems studied: PVC2 < PVC5 < PVC3 < PVC4. In general, all weight losses observed for PVC-DEHF/DEHT and PCV-DEHT samples were of the same magnitude as the previously published results, or even lower [11,12,13,44,45]. For example, migration tests in distilled water conducted in the same conditions as those carried out in the present study reported a weight loss of around 0.22% to PVC/DEHP, and of ca.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…PVC-DEHT film (PVC1) had the lowest weight loss values in distilled water, followed very closely by all the other plasticized systems studied: PVC2 < PVC5 < PVC3 < PVC4. In general, all weight losses observed for PVC-DEHF/DEHT and PCV-DEHT samples were of the same magnitude as the previously published results, or even lower [11,12,13,44,45]. For example, migration tests in distilled water conducted in the same conditions as those carried out in the present study reported a weight loss of around 0.22% to PVC/DEHP, and of ca.…”
Section: Resultssupporting
confidence: 88%
“…In recent years, motivated by increasing attention to sustainability awareness and concerns regarding the massive use of petroleum-based products [9] (including plasticizers) has called for a paradigm shift towards the development of renewable-based ones, or at least partially renewable ones. In this vein, several alternatives to DEHT and toxic DEHP have been disclosed [10,11], namely tung oil- [12,13], cardanol- [14,15], poly(caprolactone)- [10], or poly(hexane succinate)-based [11] plasticizers. 2,5-Furandicarboxylic acid (FDCA) is a well-recognized sugar-based monomer that is structurally related with terephthalic acid (TPA) and the precursor of several polyesters with thermal and mechanical properties very similar to those prepared from fossil-TPA [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(hexylene succinate) is a type of novel and promising polyester plasticizer for the modication of poly(vinyl chloride) (PVC) and can be employed as an alternative of the traditional dioctyl phthalate (DOP). 17 However, few investigations concentrated on this polyester synthesized in BAILs. And not only that, the side reactions which usually happen in the post-polycondensation process limit the growth of M w of this product and restrict the further practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PVC plasticized by DOP has been widely used in leathers, cloths, toys, and other aspects. [ 14‐17 …”
Section: Introductionmentioning
confidence: 99%